Pengaruh Penggunaan Abu Bata Dan Semen Sebagai Bahan Pengisi (Filler) Terhadap Uji Karakteristik Marshall Pada Campuran Laston Lapis Antara (AC-BC) - Fachrul Willian; Muhammad Shalahuddin; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Asphalt concrete is a mixture of asphalt, coarse aggregate, fine aggregate and filler. Many types of filler have been used to improve asphalt concrete performance. In this research, a combined ofbrick ash and portland cement was used as filler. As wasted products, this mixed filler can be used as an alternative replacement of Portland cement due to their similar chemical compounds. Thespecifications used follow the 2010 revision 3 Bina Marga General Specifications standard using the Marshall method. This research combined brick ash and portland cement at ratio of 0:100,25:75, 50:50, 75:25 and 100:0, asphalt content varied were 5%, 5.5%, 6%, 6.5% and 7%. The optimum fillers contents for each variation i.e. 6.08%, 6.43%, 5.83%, 6.20% and 5.50%respectively. The results present that all variations fulfill specification. The variation suggested as a mixture is a variation off 100:0, because that variations fulfill the specified spesifications economically.Keywords: portland cement, brick ash, AC-BC, Bina Marga Specifications 2010 Revision